METHODOLOGY FOR KNOWLEDGE MEASUREMENT IN PROFESSIONAL TRAINING - Alexey V. Tomiltcev; Alexey V. Maltsev (Moscow Polytechnic University, 2016)
The article addresses the problems of methodology to measure and assess students' knowledge in accordance with the prescriptions of professional standards that are implemented in higher education system of Russia. The research problem is considered both from the position of the general theory of measurement, and the analysis of the application practice in education and other spheres of economic activity.